Simple and Universal Current Modulator Circuit for Indoor Mobile Free-Space-Optical Communications Testing - Hejduk, Stanislav; Witas, Karel; Latal, Jan; Vitasek, Jan; Bocheza, Jiri; Vasinek, Vladimir (Advances in electrical and electronic engineering, 2014)
The use of LED for illumination and communication together is more and more interesting with the increasing deployment of LEDs to our homes and industrial buildings. Modulation of this kind of light sources is difficult because of high voltage and current demands. Since the LED configurations and values of current and voltage are different, our universal modulator has to be able to operate even under these circumstances. This paper proposes simple and universal current modulator for LED lighting modulation for frequencies around 1MHz. Main objective is to allow initial testing of different types of High Power LEDs and different photodetector configurations and circuits in diffusive based Free-Space-Optical networks. In the experimental part we also compare results for some different types of LED light sources.